2011
DOI: 10.1186/1297-9716-42-116
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium infection in a veal calf cohort in France: molecular characterization of species in a longitudinal study

Abstract: Feces from 142 animals were collected on 15 farms in the region of Brittany, France. Each sample was directly collected from the rectum of the animal and identified with the ear tag number. Animals were sampled three times, at 5, 15 and 22 weeks of age. After DNA extraction from stool samples, nested PCR was performed to amplify partial 18S-rDNA and 60 kDa glycoprotein genes of Cryptosporidium. The parasite was detected on all farms. One hundred out of 142 calves (70.4%) were found to be parasitized by Cryptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 55 publications
15
38
0
1
Order By: Relevance
“…in yaks varied with age, consistent with previous surveys in dairy cattle which revealed that the prevalence of Cryptosporidium fell with increasing age [7], [15], [34], [35]. We investigated the relationship between age and Cryptosporidium species infecting 47 of the 142 samples, and found that the species obtained in this study existed in all age groups.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…in yaks varied with age, consistent with previous surveys in dairy cattle which revealed that the prevalence of Cryptosporidium fell with increasing age [7], [15], [34], [35]. We investigated the relationship between age and Cryptosporidium species infecting 47 of the 142 samples, and found that the species obtained in this study existed in all age groups.…”
Section: Discussionsupporting
confidence: 88%
“…The zoonotic subtype IIa has been found worldwide. Within the IIa subtype, IIaA15G2R1 was the most common subtype in calves which has been reported in many developed countries in North America [32], [56] and Europe [12], [15], [31], [40], [57][60]. In contrast genetic characterization of C. parvum subtypes in dairy calves differed in China, where IIdA19G1 was the only subtype which had been identified previously [16], [34].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Porcentagens de positividade superiores à evidenciada neste estudo, foram detectadas (FOLLET, et al, 2011;MURAKOSHI, et al, 2012).…”
Section: Resultsunclassified